Supporting young people through the COVID-19 pandemic and beyond: a multi-site qualitative longitudinal study - Madelyn Whyte; Emily Nichol; Lisa D. Hawke; Kelli Wuerth; Meaghen Quinlan-Davidson; Aileen O’Reilly; Joseph Duffy; Steve Mathias; JL Henderson; Skye Pamela Barbic (BMC Health Services Research)
Abstract Background Throughout the COVID-19 pandemic, youth have experienced substantial stress due to abrupt changes in education, finances, and social life, compounding pre-existing stressors. With youth (ages 15–26) often at critical points in development, they are vulnerable to long-term mental health challenges brought on by pandemic trauma. Methods To identify youth experiences throughout the pandemic and examine changes over time, we conducted semi-structured interviews among n = 141 youth in two Canadian provinces (Ontario and British Columbia) and across the country of Ireland at three time points over the course of more than one year (August 2020-October 2021). We conducted a qualitative longitudinal analysis using an inductive content approach. Results Categories identified were (1) coping with hardship; (2) opportunities for growth; (3) adapting to new ways of accessing services; (4) mixed views on the pandemic: attitudes, behaviour, and perception of policy response; (5) navigating COVID-19 information; (6) transitioning to life after the pandemic; and (7) youth-led recommendations for government and service response. The findings also reveal trends in health and wellness in accordance with prolonged periods of lockdown, changes in weather, and return to normalcy after the availability of COVID-19 vaccines. Key recommendations from youth include incorporating youth voice into decision making, communicating public health information effectively to youth, enhancing service delivery post-pandemic, and planning for future pandemics. Conclusions These results provide insights into the extensive longitudinal impacts of the COVID-19 pandemic on young people across three geographical locations. Actively involving youth in decision making roles for future pandemics or public health emergencies is critical.